Timing of veno-arterial extracorporeal membrane oxygenation support in patients with cardiogenic shock - Sundermeyer, Jonas; Kellner, Caroline; Beer, Benedikt N.; Dettling, Angela; Besch, Lisa; Blankenberg, Stefan; Eitel, Ingo; Frank, Derk; Frey, Norbert; Graf, Tobias; Kirchhof, Paulus; Krais, Jannis; et al. (European journal of heart failure, 2025)
Aims The optimal timing for implementing mechanical circulatory support (MCS) in cardiogenic shock (CS) remains indeterminate. This study aims to evaluate patient characteristics and outcome associated with the time interval between CS onset and veno-arterial extracorporeal membrane oxygenation (VA-ECMO) implementation. Methods and results In this study, patients with CS treated with MCS at 15 tertiary care centres in three countries were enrolled. Patients treated with MCS were stratified into early (<2 h), intermediate (2-12 h) and delayed (≥12-24 h) MCS implantation by using the time interval between CS onset and MCS device implementation. Adjusted logistic and Cox regression models were fitted to assess the association between timing of MCS implementation, patient characteristics and 30-day mortality. A total of 330 patients with CS treated with VA-ECMO and/or microaxial flow pump were included in this study; 20.9% received early, 55.8% intermediate, and 23.3% delayed MCS. Although crude 30-day mortality was slightly lower in patients with early MCS (58.1% vs. 64.7% vs. 64.3%), adjusted analyses showed no significant association between timing of MCS implantation and 30-day all-cause mortality (hazard ratio [HR] for early vs. intermediate MCS: 0.93, 95% confidence interval [CI] 0.59-1.46, p = 0.74; HR for early vs. delayed MCS: 1.29, 95% CI 0.78-2.13, p = 0.33). Moreover, the incidence of complications, related and unrelated to MCS, did not differ significantly among groups. Conclusion In this exploratory study of patients with CS treated with MCS, the timing of device implantation within 24 h after CS onset was not associated with mortality. This supports a restrictive MCS approach, reserving its application for patients experiencing CS deterioration despite conventional therapy.
Veröffentlicht: 24 October 2024
Gesehen am 25.04.2025